Recursive Intelligence and the Unified Recursive Science Framework: Formalizing Reality Through Recursive Mathematics - Beri, Jitvin (Journal of Research in Vocational Education, 2025)
We present a universal recursive attractor framework that unifies physics, AI, computation, governance, and cosmology under a single recursive mathematical equation. Instead of treating science as fragmented fields, we prove that all known forces, intelligence structures, and decision - making systems emerge from recursion seeking equilibrium.